Dampak Peran Ganda Buruh Tani Perempuan Terhadap Kehidupan Rumah Tangga - Muhammad Ikhsan; Waza Karia Akbar (Departement of Mathematics Education, 2023)
This study examines the impact of the dual role of women farm laborers on household life. Women in this study not only play a role as housewives, but also work as farm laborers. This condition certainly has an impact on household life. Based on this, this study aims to describe the impact of the dual role of women farm laborers on household life in Jorong Lubuk Pering Nagari Koto Baru District, Dharmasraya Regency. The approach used in this research is a qualitative approach with descriptive type. Data collection techniques were observation, interview, and document study. The unit of analysis in this research is a group, namely female laborers. The data analysis technique used is the Miles and Huberman model, namely data collection, data reduction, data presentation, and drawing conclusions. The results of the study stated that the impact of the dual role of women farm laborers on household life (1) the impact on the reproductive function, (2) the impact on the productive function, (3) the impact on the community work function.